New Paradigm of Learning Islamic Religious Education in the 21st Century: a Study of Amin Abdullah's Thought (EDUKASIA, 2023)
This research aims to explore Amin Abdullah's thoughts regarding the new paradigm of Islamic Religious Education (PAI) in the 21st century. The aim of this research is to contribute to learning for Islamic Religious Education teachers to be more open to knowledge outside their field. As such, in the learning process, they are more creative in applying approaches and methods in learning tools, processes, and evaluation. The method used in this research was a literature study, which analyzed research results from journals, proceedings, and books with the same theme. For its analysis, this research used a relatively new book by Amin Abdullah, i.e., "Methods of Religious Studies and Islamic Studies in the Contemporary Era," which is multidisciplinary, interdisciplinary, and transdisciplinary. Three findings or results were obtained from this research. First, the integration-interconnection approach developed into inter, multi, and transdisciplinary is highly relevant in meeting the needs of Islamic Religious Education in the 21st century. Second, the integration-interconnection or multi, inter, and transdisciplinary approach can be used as a reference in improving Islamic Religious Education learning. Third, the urgency of the multi, inter, and transdisciplinary approach lies in the figure of the educator (teacher or lecturer) as the spearhead of educational change because they are the ones who are in direct contact with the next generation at the grassroots and are the actors in educational change.